2020
DOI: 10.1016/j.celrep.2020.108125
|View full text |Cite
|
Sign up to set email alerts
|

Atf-6 Regulates Lifespan through ER-Mitochondrial Calcium Homeostasis

Abstract: SUMMARY Individually, dysfunction of both the endoplasmic reticulum (ER) and mitochondria has been linked to aging, but how communication between these organelles might be targeted to promote longevity is unclear. Here, we provide evidence that, in Caenorhabditis elegans , inhibition of the conserved unfolded protein response (UPR ER ) mediator, activating transcription factor ( atf ) -6 , increases lifespan … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…Loss of ire-1 or pek-1 was known to affect various basal physiology, such as secretory-protein metabolism, longevity, or development 43 - 45 ; therefore, the basal chemotaxis indices of ire-1 and pek-1 mutants seemed to decrease in the control group compared to that of N2. Unlike ire-1 or pek-1 , the atf-6 mutants were known to have extended lifespan without sensitivity to proteotoxic stress 46 , 47 , and the results of chemotaxis index were not different from that of N2. The other two mutants, sel-1 and sel-11 , also showed different chemotaxis indices from those of N2.…”
Section: Discussionmentioning
confidence: 92%
“…Loss of ire-1 or pek-1 was known to affect various basal physiology, such as secretory-protein metabolism, longevity, or development 43 - 45 ; therefore, the basal chemotaxis indices of ire-1 and pek-1 mutants seemed to decrease in the control group compared to that of N2. Unlike ire-1 or pek-1 , the atf-6 mutants were known to have extended lifespan without sensitivity to proteotoxic stress 46 , 47 , and the results of chemotaxis index were not different from that of N2. The other two mutants, sel-1 and sel-11 , also showed different chemotaxis indices from those of N2.…”
Section: Discussionmentioning
confidence: 92%
“…Recently Burkewitz et al 2020 demonstrated the loss of atf6 promotes longevity in C elegans. Interestingly, the life span extension is not through canonical proteostasis pathways but through the modulation of ER-mitochondrial calcium homeostasis.…”
Section: Atf6mentioning
confidence: 99%
“…Atf-6 regulates the ER function and lifespan through its proximal mediator, calreticulin/crt-1. As a downstream effect, the ER calcium release further leads to changes in mitochondrial dynamics and bioenergetics [169]. Not only in C elegans, another study conducted by Wang et al 2018 with human mesenchymal stem cells (hMSCs) also showed that ATF6 can control the aging through maintaining organelle homeostasis.…”
Section: Atf6mentioning
confidence: 99%
“…Moreover, ATF6 can regulate lipid biosynthesis and ER expansion suggesting a possible interplay in MAM-mediated lipid homeostasis and ER-mitochondrial physiology ( Bommiasamy et al, 2009 ). Most recently, ATF6 has also been implicated in ER-mitochondrial Ca 2+ homeostasis ( Burkewitz et al, 2020 ).…”
Section: Mitochondria-associated Endoplasmic Reticulum Membranesmentioning
confidence: 99%